Determining Overweight and Obesity Prevalence in School Children Living in Urban Areas - Melih Bozkurt; Yiğit Üngör (Çocuk Dergisi)
Objective: The aim of this study is to examine the extent of obesity in children in the Istanbul metropolitan area. In the last two decades obesity prevalence has reached peak numbers in developed countries and has still been rising in developing countries. In Turkey, there is still limited research on this topic given the prevalence of obesity in metropolitan areas. Methods: Our research was undertaken in 4 socio-economically different adjacent districts of Istanbul. Data was collected from 2,668 children in 24 different state schools. During the data collection the children’s height and weight data was recorded and later age and gender oriented body mass indexes (BMI) were calculated. BMI calculations were interpreted using Neyzi et. al. ’s (2008) percentiles which was specifically developed for Turkish children. Results: According to the results 11.5% of all children were overweight and 9.9% of children were obese. There was a statistically significant relationship between age and obesity prevalence, and gender and obesity prevalence. As children grew older, overweight and obesity prevalence decreased, however, prevalence of underweight and severely underweight children increased. Slightly more females were identified with higher overweight and obesity prevalence compared to males. Conclusion: Higher percentages of early childhood (age 6-10) obesity might be the sign of increasing obesity prevalence in Turkey. However, due to the section nature of the data, this research cannot be fully conclusive on the issue. For this reason, children’s overweight and obesity prevalence should be determined by follow up studies in large citiesin order to understand the trends of childhood obesity prevalence.